ANALISA PROSEDUR DAN KEBIJAKAN PEMBERIAN KREDIT PADA BANK PEMERINTAH DAERAH KHUSUSNYA BANKALTIM BERDASARKAN UNDANG-UNDANG PERBANKAN - Purnamayanti, Ratih Hernita (EKONOMIA, 2015)
The banking industry is one very important component of the national economy in order to maintain a balance between progress and unity of the national economy . The stability of the banking industry is affecting the stability of the overall economy .Public confidence in the national banking industry is one of the keys to maintaining the stability of the bankingIndustry so as not to trigger the onset of a crisis again . This belief can be obtained by legal uncertainty, analysis procedures and policies in the banking world are evident in bank regulation and deposit insurance customers to increase the survival of a bank is healthy . The healthy survival of a bank can ensure the safety of its customers deposits and increasing the role of banks as providers and development and banking services . If the banks lose the trust of the community so that the survival of a bank is not able to proceed , tersedbut bank into a bank failure that resulted in the revocation of their business licenses .This study aims to evaluate and learn about the effectiveness of the loan application has been decided by BANKALTIM . This study used a qualitative methodology through case study analysis technique is a comparative analysis , by comparing what the case studies examined have a common theoretical background .Procedures and policies , especially in the credit application has BANKALTIM matches banking prudential banking act and although there is a gap can cause bad credit appears that the completeness of required credit application documents related to the financial statements for the end consumer does not have adverse financial statement analysis for credit BANKALTIM more emphasis on the value of the secured collateral compared to the analysis of customer's business prospects and facilities store credit only emphasizes on the willingness of the customer to the settlement or credit due to more familiarity .In this study explained the analysis procedures and credit policies are applied to BANKALTIM which hopefully will be able to maintain public confidence in the banking industry, both in terms of the management of all forms of financial transactions , financial guarantee , as well as other services